Digital Competence, Tourism Human Resource Responsiveness, and Tourists’ Visit Decisions: The Mediating Role of Tourist Experience Quality in South Sulawesi - Hendra Gunawan; Asrianto Bakri (STIE Amkop Makassar, 2026)
This study examines the effects of digital competence and tourism human resource responsiveness on tourists’ visit decisions, with tourist experience quality acting as a mediating variable at tourism destinations in South Sulawesi. The analysis follows a simulated dataset representing 125 tourists and four reflective constructs, each measured by five indicators. Structural Equation Modeling based on Partial Least Squares (PLS-SEM) was applied. The measurement model shows outer loadings ranging from 0.795 to 0.926, Cronbach’s Alpha from 0.902 to 0.922, Composite Reliability from 0.928 to 0.942, and AVE from 0.721 to 0.764. Discriminant validity is supported by the Fornell–Larcker criterion and cross-loading patterns. In the structural model, digital competence positively affects tourist experience quality (β=0.447), tourism human resource responsiveness positively affects experience quality (β=0.441), digital competence positively affects visit decisions (β=0.239), tourism human resource responsiveness positively affects visit decisions (β=0.252), and tourist experience quality exerts the strongest positive effect on visit decisions (β=0.471); all paths are significant at p<0.001. The indirect effects of digital competence and tourism human resource responsiveness through experience quality are 0.210 and 0.208, respectively, indicating partial mediation. The R² values are 0.494 for tourist experience quality and 0.629 for visit decisions, while SRMR=0.062 and NFI=0.984 provide support for model fit. The findings indicate that digital capability and responsive human service should be managed jointly because both shape the quality of the tourist experience and, through that experience, reinforce visit decisions.